Factors affecting warthog (Phacochoerus africanus) occupancy with presence of aardvark (Orycteropus afer) as a keystone species - Keith, Mark (University of Pretoria, 2024)
Mini Dissertation (MSc (Wildlife Health, Ecology and Management))--University of Pretoria, 2024.